Updating the landscape of direct-to-consumer pharmacogenomic testing - Filipski KK; Murphy JD; Helzlsouer KJ (Dove Medical Press, 2017)
Kelly K Filipski, John D Murphy, Kathy J Helzlsouer Epidemiology and Genomics Research Program, Division of Cancer Control and Population Sciences, National Cancer Institute, Rockville, MD, USA Abstract: Pharmacogenomics has identified important drug–gene interactions that affect the safety and efficacy of medications. Direct-to-consumer genetic testing, when first introduced, included some pharmacogenomic-related genes. The current landscape of pharmacogenomic direct-to-consumer testing is reviewed. Prior published reviews of the literature were updated through February 2017 and a scan of the current availability of direct-to-consumer genomic testing by companies was conducted. Results of the review demonstrate a shift toward physician-approved ordering. Keywords: pharmacogenomics, direct-to-consumer testing